2018
DOI: 10.1183/23120541.00159-2017
|View full text |Cite
|
Sign up to set email alerts
|

Bulbar impairment score and survival of stable amyotrophic lateral sclerosis patients after noninvasive ventilation initiation

Abstract: There is general agreement that noninvasive ventilation (NIV) prolongs survival in amyotrophic lateral sclerosis (ALS) and that the main cause of NIV failure is the severity of bulbar dysfunction. However, there is no evidence that bulbar impairment is a contraindication for NIV. The aim of this study was to determine the effect of bulbar impairment on survival in ALS patients with NIV.ALS patients for whom NIV was indicated were included. Those patients who refused NIV were taken as the control group.120 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 34 publications
2
32
0
2
Order By: Relevance
“…(70 NIV users, 52 non-users, total N = 122) ( 11 ), the studies by Bourke et al ( 26 , 39 ), which had an enrollment of 15 and 92 subjects, respectively. All of the other NIV studies also had samples sizes of <100 [e.g.,( 16 , 28 , 29 , 40 )]. The large sample size of the present study provides confidence in the associative survival benefit of NIV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(70 NIV users, 52 non-users, total N = 122) ( 11 ), the studies by Bourke et al ( 26 , 39 ), which had an enrollment of 15 and 92 subjects, respectively. All of the other NIV studies also had samples sizes of <100 [e.g.,( 16 , 28 , 29 , 40 )]. The large sample size of the present study provides confidence in the associative survival benefit of NIV.…”
Section: Discussionmentioning
confidence: 99%
“…Such a large cohort enables statistically relevant analysis of the ideal FVC %predict threshold for initiating Bi-PAP, the optimal daily Bi-PAP usage time (hours/day), and the evaluation of the adjunctive usage of cough assist for secretion clearance. In fact, cough assist in particular has been highly litigated, particularly in bulbar ALS populations ( 27 29 ) where it could carry a higher risk. The goal is to make recommendations regarding NIV (including Bi-PAP and cough assist) initiation and usage that maximize associative survival benefit.…”
Section: Introductionmentioning
confidence: 99%
“…Survival differences in favour of pressure assist‐control ventilation have been observed in large patient cohorts with a follow‐up of 10 years (+13 months under pressure‐controlled ventilation vs +10 months under volume‐controlled ventilation), although other factors including regional and cultural differences probably account for this finding.…”
Section: How Should Als Patients Be Ventilated?mentioning
confidence: 99%
“…[9][10][11] It has also been shown that NIV might also delay respiratory decline. [9][10][11] It has also been shown that NIV might also delay respiratory decline.…”
Section: Ventilation Parametersmentioning
confidence: 99%
“…Overall median ventilation times increased significantly from with much larger number of patients suggest a higher prolongation of survival between 11 and 15.5 months and in bulbar patients as well. [9][10][11] It has also been shown that NIV might also delay respiratory decline. 12 Recent studies suggested that NIV should be applied as early as possible and that (opposed to former guideline…”
Section: Ventilation Parametersmentioning
confidence: 99%